Loss Aversion and the Welfare Ranking of Policy Interventions - Sergio Firpo; Antonio F. Galvao; Martyna Kobus; Thomas Parker; Pedro Rosa-Dias (Institute of Labor Economics (IZA), 2020)
In this paper we develop theoretical criteria and econometric methods to rank policy interventions in terms of welfare when individuals are loss-averse. The new criterion for "loss aversion-sensitive dominance" defines a weak partial ordering of the distributions of policy-induced gains and losses. It applies to the class of welfare functions which model individual preferences with non-decreasing and loss-averse attitudes towards changes in outcomes. We also develop new statistical methods to test loss aversion-sensitive dominance in practice, using nonparametric plug-in estimates. We establish the limiting distributions of uniform test statistics by showing that they are directionally differentiable. This implies that inference can be conducted by a special resampling procedure. Since point-identification of the distribution of policy-induced gains and losses may require very strong assumptions, we also extend comparison criteria, test statistics, and resampling procedures to a partially-identified case. Finally, we illustrate our methods with an empirical application to welfare comparison of two income support programs.
Keywords: C12; C14; I30; 330; welfare; loss aversion; policy evaluation; stochastic ordering; directional differentiability